2018
DOI: 10.1002/2211-5463.12497
|View full text |Cite
|
Sign up to set email alerts
|

2D DIGE proteomic analysis reveals fasting‐induced protein remodeling through organ‐specific transcription factor(s) in mice

Abstract: Overnight fasting is a routine procedure before surgery in clinical settings. Intermittent fasting is the most common diet/fitness trend implemented for weight loss and the treatment of lifestyle‐related diseases. In either setting, the effects not directly related to parameters of interest, either beneficial or harmful, are often ignored. We previously demonstrated differential activation of cellular adaptive responses in 13 atrophied/nonatrophied organs of fasted mice by quantitative PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Beta-actin protein level was increased in our experiment, however, not at mRNA level which might be at connection to promote villus remodeling or might be a result of an increased protein anabolism caused by fasting. Kamata et al (2018) also found increased protein levels of several structural proteins (e.g., actin, annexin, collagen, keratin, moesin) in the peripheral organs of mice fasted for 24 h. Keratins are important proteins for stress protection in the colonic epithelium (Asghar et al, 2015) and their expression is upregulated after different stress sources (Helenius et al, 2016). Increased expression of KRT14 was observed in our experiment and it may be in connection with the increased stress caused by fasting and for the stress protection of villus structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta-actin protein level was increased in our experiment, however, not at mRNA level which might be at connection to promote villus remodeling or might be a result of an increased protein anabolism caused by fasting. Kamata et al (2018) also found increased protein levels of several structural proteins (e.g., actin, annexin, collagen, keratin, moesin) in the peripheral organs of mice fasted for 24 h. Keratins are important proteins for stress protection in the colonic epithelium (Asghar et al, 2015) and their expression is upregulated after different stress sources (Helenius et al, 2016). Increased expression of KRT14 was observed in our experiment and it may be in connection with the increased stress caused by fasting and for the stress protection of villus structure.…”
Section: Discussionmentioning
confidence: 99%
“…Feed restriction can cause a decrease in APOA1 expression in chicken liver as investigated by Richards et al (2003). In contrast, expression of APOA1 was found to be increased after 48 h fasting in various mouse tissues (Kamata et al, 2018). In our experiment, an increased expression of APOA1 might be related to the increased homeostatic need for reverse cholesterol transport triggered by 24 h fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Such CSF alterations could reflect some degree of dysfunction in the blood-CSF barrier or amino acid metabolism within the brain; Cbs is substantially expressed within the brain. 11) These findings may contribute to the understanding of CNS disorders in Cbs −/− mice and homocystinuria patients.…”
Section: Discussionmentioning
confidence: 85%
“…from independent mouse samples (sample numbers in parentheses) with significant differences between the genotypes (* p < 0.05, ** p < 0.01, and *** p < 0.001) and the BW groups ( # p < 0.05 and ### p < 0.001) using Student's t-test. homocystinuria, 11) and hepatic steatosis 7,9) ; however, most of them die by 2 weeks of age due to unknown mechanisms. 7,9) Although serum levels of alanine aminotransferase, aspartate aminotransferase, and triglyceride were all higher in 2-weekold Cbs −/− pups than wild-type pups (369 versus 13.2 [IU/L], 432 versus 61.8 [IU/L], and 226 versus 91.9 [mg/dL], respectively), 8) and some differential proteins exist in serum, including α-fetoprotein, 12) such changes should not be the primary cause of the death.…”
Section: Discussionmentioning
confidence: 99%
“…Although several immune-related genes were downregulated in starved fish, complement proteins c6 and c7 were both significantly upregulated in starved fish (Table S3) shown to be induced in mouse livers upon fasting, and reduced in the livers of ground squirrels preparing for hibernation 72,73 . Of the 11 genes differentially expressed in 3dpR refed fish compared to fed controls, 6 were also differentially expressed at 21dpS including prss59.1, prss59.2, and bco2l.…”
Section: Starvation and Refeeding Leads To Distinct Changes In Intestmentioning
confidence: 99%